Diachronic variation in secondary burial practices in Bronze and Iron Age Moravia. (October 2018) - Pankowská, Anna
Abstract: The transition from inhumation to cremation is a well-documented phenomenon in Bronze Age Central Europe. However, almost nothing is known about similar transitions taking place in other mortuary practices, such as secondary burials. This study brings new insights into diachronic trends in secondary burials during the Central European Bronze and Iron Age. Diachronic trends in secondary burials are defined here by different kinds of excarnation. The type of excarnation was observed in 23 secondary burials dating to the Early Bronze Age and the turn of the Late Bronze to Early Iron Age at five sites in Moravia (Czech Republic). Osteological and taphonomic assessment of unburned human bones recovered from settlement contexts indicates a changing pattern of secondary burial practice over time. Early Bronze Age human remains bear traces of both passive excarnation by natural agents, such as exposure to carnivores, and excarnation by primary burial. By the Late Bronze Age and Early Iron Age secondary burials show evidence of excarnation with tools. This modification of secondary burial practices, may be connected with a contemporaneous change of primary burial practices from inhumation to cremation. Highlights: Variations in primary and secondary burials occur over the course of the Bronze Age in Moravia. Changes in excarnation method defines variations in secondary burials. Early Bronze Age secondary burials resulted from passive excarnation by natural agents. Late Bronze and Iron Age secondary burials resulted from active excarnation with tools. The shift in secondary rituals may correlate to the shift from inhumation to cremation.